USER GENERATED CONTENT ANALYSIS AND MARKETING STRATEGIES AND THEIR IMPLICATIONS IN THE EXISTENCE OF AIR PHILM (Case Study: KKN Film in Danari Village) - Nabilahpurba, Nabilahpurba; Lubis, Fauzi Arif; Nurbaiti, Nurbaiti (Universitas Ibn Khladun Bogor, 2023)
The research aims to analyze the extent to which the role of user generated content in developing marketing strategies as Internet technology progresses as well as the implications of the application of user-generated content into the existence of home films. The research method used is a qualitative method with a descriptive scale that uses a case study approach. Data collection in this study was obtained through the observation of literature sources and other documentation related to consumer interest in making purchasing decisions. The results show that user generated content plays an important role in developing a business strategy. This is proved by the expression of a film producer who has already received very satisfactory results. The User Generated Content strategy has become a strategy that has a major impact on film production because User generated content plays an active role in its promotion process. Some important roles of user generated content are: 1) Increase traffic organically 2) More consumer confidence 3) Save costs. And the implication is being able to introduce the existence of a hometown film with a short duration of time that is able to make a lot of people feel curious to watch the movie.